Energetické využití slunečního záření v Jihomoravském kraji , posouzení vlivů na životní prostředí - Kučerová, Simona (Vysoké učení technické v Brně. Fakulta chemická, 2010)
Práce je zaměřena na analýzu bilance sluneční energie pro JmK. Práce analyzuje potencionální a reálné možnosti termického a fotovaltaického využití solární energie v návaznosti na územně energetickou koncepci rozvoje kraje.

This thesis deals with analyses of solar energy balance in the South Moravian Region. Analyses potential and real possibilities of termal and fotovoltaic systems of the South Moravian Region in cooperation with the Territorial energy conception of region development.
Utilizable solar energy for area - South Moravia, appraisal impact on the environment
Keywords: Obnovitelné zdroje energie (OZE); solární (sluneční) energie; termika; fotovoltaika; Renewable resources energy (RRE); solar (sun) energy; termic; fotovoltaic